2007
DOI: 10.1111/j.1399-0039.2007.00867.x
|View full text |Cite
|
Sign up to set email alerts
|

Relative predispositional effects of HLA class II DRB1‐DQB1 haplotypes and genotypes on type 1 diabetes: a meta‐analysis

Abstract: The direct involvement of the human leukocyte antigen class II DR-DQ genes in type 1 diabetes (T1D) is well established, and these genes display a complex hierarchy of risk effects at the genotype and haplotype levels. We investigated, using data from 38 studies, whether the DR-DQ haplotypes and genotypes show the same relative predispositional effects across populations and ethnic groups. Significant differences in risk within a population were considered, as well as comparisons across populations using the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
161
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(179 citation statements)
references
References 69 publications
14
161
4
Order By: Relevance
“…8,14,[29][30][31][32] Earlier studies derived a HLA DR-DQ haplotype-based risk strategy, which showed a statistically significant risk hierarchy, ranging from highly predisposing to highly protective. 33,34 The need for at least three HLA DQ-DRbased risk groups was noticed by other groups, as well. 31,35,36 As this study focused exclusively on the HLA DQ region, which shows a high density of polymorphisms, a grouping based only on HLA DQ risk status was applied (see Supplementary data).…”
Section: Discussionmentioning
confidence: 99%
“…8,14,[29][30][31][32] Earlier studies derived a HLA DR-DQ haplotype-based risk strategy, which showed a statistically significant risk hierarchy, ranging from highly predisposing to highly protective. 33,34 The need for at least three HLA DQ-DRbased risk groups was noticed by other groups, as well. 31,35,36 As this study focused exclusively on the HLA DQ region, which shows a high density of polymorphisms, a grouping based only on HLA DQ risk status was applied (see Supplementary data).…”
Section: Discussionmentioning
confidence: 99%
“…The most important susceptibility factors reside within the major histocompatibility complex (MHC) where particular human leukocyte antigen (HLA) class II DRB1-DQA1-DQB1 haplotypes confer high disease risk. 1,2 However, numerous studies have strongly implicated additional T1D risk loci within the MHC. [3][4][5][6][7][8][9][10][11][12] This complex contains an unusually high density of genes involved in immunological responses, 13 of which many are good candidates for involvement in autoimmune processes.…”
Section: Introductionmentioning
confidence: 99%
“…T1D is genetically strongly associated with HLA-DQ2 and HLA-DQ8 (13,14). HLA-DQ2/8 heterozygous individuals carry the highest odds ratio (OR) for T1D, exceeding that of HLA-DQ2 or HLA-DQ8 homozygous individuals (13,15).…”
Section: Posttranslational Modification Of Hla-dq Binding Islet Autoamentioning
confidence: 99%